Keputusan Nasabah dalam Menabung di Bank Konvensional di daerah Istimewa Yogyakarta - Jonathan Herdioko (Jurnal Riset Manajemen dan Bisnis, 2017)
The purpose of this study is to examine the antecedent of customer’s decision to save their assets in conventional banks. Variables analized preceded product, place, and promotion toward customers’ decision. Data for this study were collected by offline administered survey to 300 respondents in five districts in Yogyakarta Special Region. They are Gunung Kidul, Kulon Progo, Sleman, Bantul, and  Yogyakarta. The hyphotesis testing was conducted using the multiple regression analysis. Findings of this study indicate that product, place, and promotion have strong influence on customers decision to save their assets in conventional banks.Keyword: conventional bank, customers decision, multiple regressions analysis